Identification and prediction of alternative transcription start sites that generate rod photoreceptor-specific transcripts from ubiquitously expressed genes. - Evgenya Y Popova; Anna C Salzberg; Chen Yang; Samuel Shao-Min Zhang; Colin J Barnstable (PLoS ONE)
Transcriptome complexity is substantially increased by the use of multiple transcription start sites for a given gene. By utilizing a rod photoreceptor-specific chromatin signature, and the RefSeq database of established transcription start sites, we have identified essentially all known rod photoreceptor genes as well as a group of novel genes that have a high probability of being expressed in rod photoreceptors. Approximately half of these novel rod genes are transcribed into multiple mRNA and/or protein isoforms through alternative transcriptional start sites (ATSS), only one of which has a rod-specific epigenetic signature and gives rise to a rod transcript. This suggests that, during retina development, some genes use ATSS to regulate cell type and temporal specificity, effectively generating a rod transcript from otherwise ubiquitously expressed genes. Biological confirmation of the relationship between epigenetic signatures and gene expression, as well as comparison of our genome-wide chromatin signature maps with available data sets for retina, namely a ChIP-on-Chip study of Polymerase-II (Pol-II) binding sites, ChIP-Seq studies for NRL- and CRX- binding sites and DHS (University of Washington data, available on UCSC mouse Genome Browser as a part of ENCODE project) fully support our hypothesis and together accurately identify and predict an array of new rod transcripts. The same approach was used to identify a number of TSS that are not currently in RefSeq. Biological conformation of the use of some of these TSS suggests that this method will be valuable for exploring the range of transcriptional complexity in many tissues. Comparison of mouse and human genome-wide data indicates that most of these alternate TSS appear to be present in both species, indicating that our approach can be useful for identification of regulatory regions that might play a role in human retinal disease.